Brida : a novel - Costa, Margaret Jull (ill., 2008)
The story of a young Irish girl who dives into sorcery and experiments with different magical traditions. She meets a wise man who dwells in a forest, who teaches her about overcoming her fears and trusting in the goodness of the world; and a woman who teaches her how to dance to the music of the world, and how to pray to the moon. As she seeks her destiny, she struggles to find a balance between her relationships and her desire to become a witch.